Ameletus Mayflies (Ephemeroptera: Ameletidae) of the Eastern Nearctic - David H. Funk (Insects)
Fourteen Ameletus species are recognized in the eastern Nearctic (south of the Artic zone), including six described as new. Keys to adult males and full-grown larvae are provided. Taxonomic decisions were based on morphologic and genetic evidence. Their justification is discussed in depth and four species groups are proposed. The vast majority of Ameletus encountered in the eastern Nearctic are members of one of three triploid, clonal parthenogenetic species, at least two of which are of hybrid origin. Bisexual progenitors of the parthenogens were inferred using a combination of mitochondrial and nuclear genetic markers. The parthenogens likely arose during the Late Pleistocene when glacial advances brought previously allopatric species/populations into contact, and as glaciers retreated the parthenogens rapidly expanded their range while the sexual lineages remained in presumed glacial refugia. Although parthenogenesis is relatively common in Ephemeroptera, these Ameletus represent the first known cases of polyploidy and hybrid origin.